HIGH DENSITY POROUS POLYETHYLENE FACIAL IMPLANTS (PPAD) IN OROFACIAL HARMONIZATION: LITERATURE REVIEW - Flávio de Oliveira e Oliveira, Victor; dos Santos Souza, Aldenízia; Vitória Santana Santos, Ana; Lopes Leite, Gleison; Paulo Mello Lócio, João; Marita Ribeiro de Amorim, Julia; Natágoras Alves de Albuquerque, Marcone; Beatriz Araújo de França, Maria; Gomes de Sousa, Mauri; Dannylo Macedo Rodrigues, Welber (Health and Society, 2023)
This work constitutes a literature review that explores the significance of Orofacial Harmonization Procedures (OHP) utilizing High-Density Porous Polyethylene Facial Implants (HDPE) to enhance facial aesthetics, contouring, rejuvenation, and volume augmentation. The paper addresses both theoretical and practical aspects of these procedures, providing insights into surgical technique, anatomy of treated areas, pre-operative assessment, anesthesia, pharmacology, medication, post-operative care, and potential complications. The review underscores the role of facial aesthetics in forming initial impressions and how aesthetic dental procedures within OHP are gaining popularity to achieve such harmony. It also emphasizes the integration of positive psychology in understanding aesthetic procedures, considering the positive psychological impacts on patients’ self-esteem and confidence. The work comprehensively discusses the use of HDPE as an alloplastic material for facial implants, elucidating its attributes such as the porous structure enabling implant vascularization and incorporation, along with its superiority over other materials in terms of inflammation and durability. Practical aspects of performing these procedures are addressed, encompassing commonly treated areas (chin, jaw, cheek), incision and suture techniques, anesthesia selection, antibiotic administration, and pre- and post-operative care. Furthermore, potential complications are presented, including improper patient selection, edema, infection, migration, extrusion, and others. The study highlights the significance of proper patient selection, surgical technique, and post-operative care for successful HDPE facial implant procedures. The review concludes that this technique can yield significant benefits in enhancing patients’ self-esteem and appearance, yet underscores the importance of adequate professional training and rigorous monitoring to prevent complications.